Molecular mechanisms underlying the valproic acid-induced degradation of transcriptional coactivators p300 and CBP - St-Germain, Jonathan R (University of Ottawa (Canada), 2006)
p300 and CBP are closely related transcriptional coactivators involved in a wide range of cellular processes. They interact with a large array of transcription factors and possess intrinsic acetyltransferase activity which allows them to acetylate many nuclear proteins including nucleosomal histones. Although much is known about the functions of p300 and CBP, what in turn regulates these coactivators is less understood. The present study reveals that the stability of both proteins is affected by the histone deacetylase inhibitor valproic acid and elucidates the molecular mechanisms involved in this pathway. These results show that valproic acid induces degradation of p300 and CBP through the 26S proteasome, and suggest that this occurs in an ubiquitin-dependent manner and that this effect is mediated by the B56gamma3 regulatory subunit of protein phosphatase 2A. Considering the involvement of valproic acid, p300 and CBP in such processes as embryonic development and tumorigenicity, these findings potentially entail important biological significance.
Keywords: Biology, Molecular.